2004
DOI: 10.2135/cropsci2004.7320
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the Expression of Acyl‐ACP Thioesterase Transgenes in Oilseed Rape Doubled Haploid Lines

Abstract: stable for more than five generations, without any apparent genetic instability or loss of the transgenic pheno-Transgene stability in doubled haploid (DH) lines is an important type. However, instability in the expression of other consideration for transgenic cultivar development programs. The objective of this study was to assess the expression stability of acyl-acyl transgenes has been observed in some studies (Assaad carrier protein (ACP) thioesterase (TE) transgenes in oilseed rape Scheid et al., 1991; Zh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…They ascribed this behavior to the use of CaMV–35S promoter driving the transgene. Transgene silencing has also been reported by other investigators [44, 45], with this as well other promoters, e.g., CaMV–35S [45, 46], Act1D [44], and maize ubi1 [43, 47], with different transformation methods, such as Agrobacterium -mediated transformation of oilseed rape [48, 49] and microprojectile bombardment for wheat [43, 47]. These reports and the current study support the conclusion that transgene silencing is not correlated to any specific promoter or transformation method used.…”
Section: Discussionsupporting
confidence: 84%
“…They ascribed this behavior to the use of CaMV–35S promoter driving the transgene. Transgene silencing has also been reported by other investigators [44, 45], with this as well other promoters, e.g., CaMV–35S [45, 46], Act1D [44], and maize ubi1 [43, 47], with different transformation methods, such as Agrobacterium -mediated transformation of oilseed rape [48, 49] and microprojectile bombardment for wheat [43, 47]. These reports and the current study support the conclusion that transgene silencing is not correlated to any specific promoter or transformation method used.…”
Section: Discussionsupporting
confidence: 84%
“…Temperatures in the greenhouse in both the fall and spring greenhouse cycles averaged approximately 208C, near to the optimum temperature for maximum phenotypic expression for oil, protein, erucic acid and glucosinolate concentrations (Canvin 1965;Mailer and Wratten 1985;Tang et al 2004). The means for all seed quality traits for fall and spring greenhouse cycles were not significantly different, so the experiments from the two greenhouse cycles were combined to increase sample size and simplify data presentation.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Wilmer et al (1996) reported that that erucic acid concentration of the rapeseed cultivar Reston decreased as temperature increased from 15 to 258C in controlled environment studies. Tang et al (2004) also reported that very long chain fatty acids (C 20 and higher) decreased when temperature increased from 208C/158C day/night to 258C/208C day/night for cross progeny involving the rapeseed cultivar Mercury. Field experiments have shown that rapeseed exhibits significant cultivar and site variability in seed quality (Mailer and Wratten 1985;Shi et al 2003).…”
mentioning
confidence: 92%
“…Success of these transgenic approaches has been affected by various factors that include the insertion number, the location of the transgene in the genome and the stability of the desired trait [51] . While genetic transformation has resulted in some success in modifying fatty acid composition [54,58,59] , limitations are encountered during attempts to increase seed oil content [16,35] .…”
Section: Approaches Used To Improve Canola Oilmentioning
confidence: 99%